Undarobius, a new genus of cavernicolous weevils (Curculionidae: Entiminae: Leptopiini) from the Undara Lava Caves in north-eastern Australia, with an overview of anophthalmic and microphthalmic Australian Curculionidae - Escalona, Hermes E.; Oberprieler, Rolf G. (Zootaxa, 2021)
Undarobius gen. n., a new genus of cavernicolous weevils with two new species, U. howarthi sp. n. and U. irvini sp. n., is described from the Undara Lava Cave system in north-eastern Queensland, Australia. These are the first cavernicolous weevils to be described from Australia, and U. howarthi is a new addition to the rich arthropod fauna of Bayliss Cave. Undarobius weevils are relatively large in size (4.0–5.5 mm long), anophthalmic and apterous with a robust, flattened body and long legs. The genus has affinities with Leptopiini, but its placement in the tribe is uncertain. We also provide a list of the known anophthalmic and microphthalmic weevils in Australia, spanning 65 species classified in 20 genera, eight tribes and about seven subfamilies and found in diverse hypogean habitats, mainly leaf litter but also soil, beach sand, subterranean aquifers and mosses.